Pengaruh Efikasi Diri terhadap Kemampuan Eksplorasi Karier di Kalangan Remaja - Egriyanto Samuel Lami; Rizky M.A. Abel; Paulinus A.S. Uda; Febriana Febriana (Prodi Bimbingan Konseling FKIP UNDANA, 2025)
Self-efficacy is a person's belief in his or her ability to complete tasks and achieve success. Self-efficacy can help individuals explore different types of career fields that he or she may be able to enter. In this study to find out 1) the efficacy description 2). Overview of career exploration skills 3) the effect of self-efficacy on the career exploration ability of adolescents in the TDM 1 Kupang City Area. This study uses a quantitative approach with a descriptive test research design and a simple linear regression test. The population in this study is 62 adolescents. The data collection technique used in this study is the Likert scale. The effect of selfefficacy on career exploration ability. The results of this study show 1) that self-efficacy is in the high category with a total of 27 adolescents out of 62 respondents with a percentage of 43.54% 2) confidence is more dominant in the low category with a total of 29 adolescents with a percentage of 47% 3) there is a significant influence of self-efficacy on the career exploration ability of adolescents in the TDM 1 Kupang City Area. Based on the results of this study, it can be concluded that 1) the description of self-efficacy is in the high category, 2) the description of career exploration ability is in the low category, 3) there is a significant influence of self-efficacy on the career exploration ability of adolescents in the TDM 1 Kupang City Area. The results of the analysis of Table F were 4.00. Because F counts 6,074 > F table, there is an effect of self-efficacy on the ability to explore the career of Adolescents in the TDM 1 Kupang City Area. Furthermore, the influence of variable X and variable Y is 0.37.3. This shows that self-efficacy has a strong influence of 0.37.3%=37 on career exploration ability while the remaining 0.62.7% is influenced by other factors, such as environment, peers, and academic grades.